Organic RFID Based on Traceability System of Rice Supply Chain - Yi-neng Chen; Kui Fang; De-hong Ding; Xing-hui Zhu; Yu-kun Yang (Institute of Advanced Engineering and Science, 2014)
Organic RFID tags have the features of two-dimensional bar codes, inexpensive, flexible and thin, while also integrated the merits of inorganic RFID tags, making them promising in facilitating the wide application of RFID technology. In this paper, organic RFID technology and its characteristics are analyzed, and the feasibility of its application in rice tracing is studied. Based on the analysis of characteristics of each links in rice supply chain, and with organic RFID technology as tracing means, a rice supply chain tracing system is designed using database and sensors. Focusing on characteristics of major links in tracing and the requirements of electronic tags, application scheme of the system is proposed for the tracking and tracing of links in rice supply chain. In the meantime, schemes are designed for the association of major information in the tracing system to ensure the accuracy and reliability of tracking and tracing. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.5115